Italian Renaissance sculpture - Olson, Roberta J. M. (London : Thames and Hudson, 2002)
The sculptors of the Italian Renaissance transformed their Classical and regional heritage. From about 1260 to 1600, these masters introduced revolutionary innovations in freestanding figures and portraits, while on reliefs convincing perspective was rendered for the first time, predating its use in painting. The Renaissance notion of the artist as genius is vividly embodied in contemporary sculptors, from Nicola Pisano through Brunelleschi and Donatello to Michelangelo.
and Giambologna. Roberta Olson surveys the extraordinary artistic achievements of the period, which were to affect for ever after the practice of Western art.
Introduction: Setting the Scene -- The First Stage of the Renaissance -- The Mature Renaissance: Beginning the Second Stage -- The Spread of the Renaissance -- Donatello: The Great Innovator -- Sculpture in Mid-Fifteenth Century Florence -- Embellishment: Late Quattrocento Florence -- Renaissance Fever outside Florence, 1450-1500 -- The High Renaissance -- Michelangelo -- The Sixteenth Century and the Legacy of Michelangelo.
Includes bibliographical references (pages 213-214) and index.
Keywords: Sculpture, Italian; Sculpture, Renaissance -- Italy